2013
DOI: 10.1016/j.conb.2013.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune signaling: a key component of alcohol abuse

Abstract: Molecular and behavioral studies corroborate a pivotal role for the innate immune system in mediating the acute and chronic effects of alcohol and support a neuroimmune hypothesis of alcohol addiction. Changes in expression of neuroimmune genes and microglial transcripts occur in post-mortem brain from alcoholics and animals exposed to alcohol, and null mutant animals lacking certain innate immune genes show decreased alcohol-mediated responses. Many of the differentially expressed genes are part of the toll l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
134
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(152 citation statements)
references
References 67 publications
(81 reference statements)
8
134
1
2
Order By: Relevance
“…Interestingly, despite its inability to antagonize opioid receptors, (+) naloxone was found to reduce stimulant-induced locomotor activity (Chatterjie, Alexander, Sechzer, & Lieberman, 1996;Chatterjie, Sechzer, Lieberman, & Alexander, 1998), which is congruent with findings suggesting that TLR4 contributes to the acute effects of drugs of abuse (Hutchinson et al, 2012) and the ability of opioid receptor antagonists to affect such responses (Wu et al, 2012). The activation of TLR4 predominantly contributes to glial activation and the subsequent release of numerous proinflammatory cytokines (Mayfield et al, 2013). Importantly, these TLR4-related processes are involved in the behavioral and neuroinflammatory effects of drugs of abuse (Mayfield et al, 2013), as TLR4 activation has been shown to be integral to alcohol-induced glial activation and proinflammatory signaling (Alfonso-Loeches, Pascual-Lucas, Blanco, Sanchez-Vera, & Guerri, 2010;Blanco, Pascual, Valles, & Guerri, 2004;Blanco, Valles, Pascual, & Guerri, 2005;Fernandez-Lizarbe, Pascual, & Guerri, 2009), as well as alcohol's behavioral effects in rodents (Wu et al, 2012).…”
Section: Naltrexone/naloxonesupporting
confidence: 73%
See 2 more Smart Citations
“…Interestingly, despite its inability to antagonize opioid receptors, (+) naloxone was found to reduce stimulant-induced locomotor activity (Chatterjie, Alexander, Sechzer, & Lieberman, 1996;Chatterjie, Sechzer, Lieberman, & Alexander, 1998), which is congruent with findings suggesting that TLR4 contributes to the acute effects of drugs of abuse (Hutchinson et al, 2012) and the ability of opioid receptor antagonists to affect such responses (Wu et al, 2012). The activation of TLR4 predominantly contributes to glial activation and the subsequent release of numerous proinflammatory cytokines (Mayfield et al, 2013). Importantly, these TLR4-related processes are involved in the behavioral and neuroinflammatory effects of drugs of abuse (Mayfield et al, 2013), as TLR4 activation has been shown to be integral to alcohol-induced glial activation and proinflammatory signaling (Alfonso-Loeches, Pascual-Lucas, Blanco, Sanchez-Vera, & Guerri, 2010;Blanco, Pascual, Valles, & Guerri, 2004;Blanco, Valles, Pascual, & Guerri, 2005;Fernandez-Lizarbe, Pascual, & Guerri, 2009), as well as alcohol's behavioral effects in rodents (Wu et al, 2012).…”
Section: Naltrexone/naloxonesupporting
confidence: 73%
“…Several studies have demonstrated that neuroinflammation plays a role in alcohol use and abuse, with chronic alcohol use being associated with microglia activation and increased innate immune cell signaling (Mayfield, Ferguson, & Harris, 2013). Glial cell line-derived neurotrophic factor (GDNF) is a protein that is essential for the maintenance and survival of dopamine (DA) neurons (Boger et al, 2006) and can inhibit microglial activation (Rocha, Cristovão, Campos, Fonseca, & Baltazar, 2012).…”
Section: Neuroinflammation and Alcohol Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, acute EtOH exposure–induced endotoxin responses are reduced by antibiotic treatment reducing gut bacteria (Rivera et al., 1998). Increased systemic endotoxin and blood cytokines impact brain cytokines and microglia (Mayfield et al., 2013). It is possible our CORT response to stress is maximal, preventing further increases by endotoxin or other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune signaling cytokines alter EtOH consumption (Marshall et al., 2017, 2017), and cytokine receptors contribute to stress‐induced EtOH consumption (Karlsson et al., 2017). Further, immune signaling molecules are increased in postmortem human alcoholic brain (Crews et al., 2017) and regulate preference for alcohol drinking in animal studies (Mayfield et al., 2013). Cytokines also enhance stressful emotional states following alcohol withdrawal (Breese et al., 2008).…”
Section: Discussionmentioning
confidence: 99%